2017
DOI: 10.3390/agronomy7020033
|View full text |Cite
|
Sign up to set email alerts
|

Applying New Technologies to Transform Blueberry Harvesting

Abstract: Abstract:The growth of the blueberry industry in the past three decades has been remarkably robust. However, a labor shortage for hand harvesting, increasingly higher labor costs, and low harvest efficiencies are becoming bottlenecks for sustainable development of the fresh market blueberry production. In this study, we evaluated semi-mechanical harvesting systems consisting of a harvest-aid platform with soft fruit catching surfaces that collected the fruit detached by portable, hand-held, pneumatic shakers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 20 publications
1
36
1
Order By: Relevance
“…Controlled impact tests that simulated mechanical harvest of currently grown SHB cultivars found cultivar differences in susceptibility to bruising; 'Farthing' (used in the present study) was moderately susceptible to bruising from single impacts of 60 or 120 cm onto a hard surface, while impacts onto a cushioning pad reduced bruise incidence by about 2/3 for both drop heights [8]. Other factors reported to contribute to higher packout rates include specialized pruning practices, and availability of cultivars with firmer fruit and with longer pedicels that facilitate better contact with the harvester (reducing the amount of red and green fruit removed during harvest) [11,15]. Two previous studies demonstrated the critical role of soft catch surfaces in reducing bruising in SHB blueberries [9,11].…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Controlled impact tests that simulated mechanical harvest of currently grown SHB cultivars found cultivar differences in susceptibility to bruising; 'Farthing' (used in the present study) was moderately susceptible to bruising from single impacts of 60 or 120 cm onto a hard surface, while impacts onto a cushioning pad reduced bruise incidence by about 2/3 for both drop heights [8]. Other factors reported to contribute to higher packout rates include specialized pruning practices, and availability of cultivars with firmer fruit and with longer pedicels that facilitate better contact with the harvester (reducing the amount of red and green fruit removed during harvest) [11,15]. Two previous studies demonstrated the critical role of soft catch surfaces in reducing bruising in SHB blueberries [9,11].…”
Section: Discussionmentioning
confidence: 90%
“…Other factors reported to contribute to higher packout rates include specialized pruning practices, and availability of cultivars with firmer fruit and with longer pedicels that facilitate better contact with the harvester (reducing the amount of red and green fruit removed during harvest) [11,15]. Two previous studies demonstrated the critical role of soft catch surfaces in reducing bruising in SHB blueberries [9,11]. Handheld, pneumatic shakers were used to harvest blueberries that were collected in a portable frame (W = 1.0 m by L = 1.5 m) with a net fabric or neoprene sheet fabric stretched across the frame.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations